The Influence of Digital Literacy, Self-Regulation, and Independent Learning on the Understanding of Technological, Pedagogical, and Content Knowledge (TPACK) Among Economics Education Students as Prospective Economics Teachers - Meri Erania Elkosi; Ani Widayati (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study aims to analyze the role of digital literacy, self-regulation, and independent learning in enhancing the understanding of Technological, Pedagogical, and Content Knowledge (TPACK) among Economics Education students. The research employed a quantitative approach with a survey design. Data were collected using a four-point Likert-scale questionnaire administered to 237 students selected from a total population of 588 Economics Education students from the 2020–2023 cohorts. The research instruments were tested for validity and reliability, while data analysis was conducted using classical assumption tests and multiple linear regression. The findings reveal that digital literacy, self-regulation, and independent learning each have a positive and significant effect on students’ understanding of TPACK (p-value < 0.05). Simultaneously, these three variables exert a significant combined influence, with a coefficient of determination (R²) of 0.723, indicating that 72.3% of the variance in TPACK understanding can be explained by these independent variables. These findings emphasize that digital literacy is the most dominant factor supporting students’ readiness as prospective economics teachers who can adapt to advancements in educational technology.